2001
DOI: 10.1046/j.1365-2508.2001.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic entry port visited: a survey of practices of consultant gynaecologists in Scotland

Abstract: To assess how consultant gynaecologists working in Scotland achieve a pneumoperitoneum for laparoscopic procedures. An anonymous postal questionnaire. All consultants working in obstetrics and gynaecology in Scotland. Questionnaire analysis. There was a 92% response rate to the questionnaire. Of the respondents, 94.8% performed closed laparoscopy, one (0.8%) performed only open laparoscopy, and six (4.4%) employed both open and closed techniques. The majority worked with the patient in the lithotomy with Trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Most gynecologists continue to use the classic closed laparoscopic entry [4,5,[13][14][15][16][17], since this entry has not been shown to be inferior to any of the other newer techniques and technologies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]25]. For a successful laparoscopic entry, the closed technique requires intraperitoneal insertion of the Veress needle and establishment of 'adequate' pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most gynecologists continue to use the classic closed laparoscopic entry [4,5,[13][14][15][16][17], since this entry has not been shown to be inferior to any of the other newer techniques and technologies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]25]. For a successful laparoscopic entry, the closed technique requires intraperitoneal insertion of the Veress needle and establishment of 'adequate' pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous variations of the basic techniques and a variety of Veress needles and trocar/cannulae systems enjoy various degrees of popularity in accordance with local teaching and personal experience, expertise, comfort, and bias. Most gynecologists, worldwide, practise the closed entry technique [4,5,[13][14][15][16][17] while the open (Hasson) method is favored mostly by general surgeons. At present, there is no evidence that the closed laparoscopic entry technique is more or less dangerous than the other available methods [4-6, 8, 18-21].…”
mentioning
confidence: 99%
“…Our national questionnaire study showed considerable heterogeneity in laparoscopic entry practice despite widespread awareness of the Middlesbrough Consensus or RCOG-sourced guidance. The inconsistency, inherent throughout every step of the laparoscopic entry procedure, has been identified by previous UK-based surveys [90][91][92][93]. Fundamentally, there was a failure to appreciate risk factors that would justify a change in entry technique as well as failure to adopt the correct safety checks after Veress insertion and before primary trocar insertion.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant variation in laparoscopic entry practice in the United Kingdom [90][91][92][93] and at international locations [27,94,95]. In an attempt to minimize the risks of laparoscopy and unify clinical practice, a number of international bodies (International Middlesbrough Consensus [96], RCOG [draft version only] [97], SOGC [78], RANZ-COG [98], EAES [99], Society of American Gastrointestinal Endoscopic Surgeons [SAGES] [100], the French Society of Endoscopic Gynecology [101], the Netherlands [102] and individual experts [103][104][105]) have recommended specific ''safe laparoscopic entry'' principles.…”
mentioning
confidence: 99%
“…The installment phase may be completed using either an open or closed approach. For closed entry laparoscopy, blind insertion of a Veress needle remains the most common method of establishing pneumoperitoneum . Correct Veress needle placement depends greatly on the experience of the laparoscopist and the anatomy and body condition of the patient .…”
mentioning
confidence: 99%